Comparative miRNAome combined with transcriptome and degradome analysis reveals a novel miRNA-mRNA regulatory network associated with starch metabolism affecting pre-harvest sprouting resistance in wheat - Longqing Sun; Ting Zhao; Dandan Qin; Jing Dong; Daorong Zhang; Xifeng Ren (BMC Plant Biology)
Abstract Background Pre-harvest sprouting (PHS) is one of the most important problems associated with the severe decrease of yield and quality under disaster weather of continuous rain in wheat harvesting stage. At present, the functions and mechanisms related to the involvement of post-transcriptional regulation has not been studied very clearly in PHS resistance. Results This study compared the differences of germinated seeds in miRNAome between the PHS-tolerant and PHS-susceptible white wheat varieties. A total of 1879 miRNAs were identified from three different stages during seed germination. In order to further obtain candidate miRNAs, the different datasets of differentially expressed miRNAs were excavated by using differential-expression and time-series analysis. Combined with degradome data, the miRNA-mRNA networks analysis was performed after genome-wide screening of target genes, and then KEGG enrichment highlighted that the starch and sucrose metabolism pathway related to PHS was specifically enriched in an especial target-gene dataset derived from R12R18-HE miRNAs. Based on transcriptome data, a network associated with starch metabolism was systematically and completely reconstructed in wheat. Then, the starch degradation pathway controlled by seven miRNA-RNA pairs were supposed to be the essential regulation center for seed germination in wheat, which also could play a critical role on the PHS resistance. Conclusion Our findings revealed the complex impact of the miRNA-mediated mechanism for forming intrinsic and inherent differences, which resulting in significant difference on PHS performance between white wheat varieties.